Wilderness reform a novel - Query, Matt; Query, Harrison 1991- (New York Emily Bestler Books/Atria, 2024)
"Thirteen-year-old Ben is sent to a remote reform program for troubled teens by a juvenile court judge. But when he arrives at the camp, located on the edge of the vast wilderness of northwestern Montana, he immediately recognizes that there is something off about the counselors. They$1 (Bre too friendly and upbeat, yet Ben can tell there$1 (Bs an undercurrent of menace. As he gets to know the boys in his cabin, he soon discovers that they each have far more going for them than whatever crime landed them there. And each has a different critical skill, one that could help them unearth what is really going on in this place$1 (Band how to make it out alive. They are inching ever closer to the truth, and the hidden evil beneath the camp$1 (Bs surface will make itself known in order to deter them." -- From Amazon.com.s
114089
Keywords: Juvenile delinquents -- Rehabilitation -- Fiction; Juvenile detention -- Montana -- Fiction; Montana -- Fiction; Horror fiction